Stem Transcriptome Reveals Mechanisms to Reduce the Energetic Cost of Shade-Avoidance Responses in Tomato - Cagnola, Juan Ignacio (2012)
While the most conspicuous response to low red/far-red ratios (R:FR) of shade light perceived by phytochrome is the promotion of stem growth, additional, less obvious effects may be discovered by studying changes in the stem transcriptome. Here, we report rapid and reversible stem transcriptome responses to R:FR in tomato (Solanum lycopersicum). As expected, low R:FR promoted the expression of growth-related genes, including those involved in the metabolism of cell wall carbohydrates and in auxin responses. In addition, genes involved in flavonoid synthesis, isoprenoid metabolism, and photosynthesis (dark reactions) were overrepresented in clusters showing reduced expression in the stem of low R:FR-treated plants. Consistent with these responses, low R:FR decreased the levels of flavonoids (anthocyanin, quercetin, kaempferol) and selected isoprenoid derivatives (chlorophyll, carotenoids) in the stem and severely reduced the photosynthetic capacity of this organ. However, lignin contents were unaffected. Low R:FR reduced the stem levels of jasmonate, which is a known inducer of flavonoid synthesis. The rate of stem respiration was also reduced in low R:FR-treated plants, indicating that by downsizing the stem photosynthetic apparatus and the levels of photoprotective pigments under low R:FR, tomato plants reduce the energetic cost of shadeavoidance responses.